PENGARUH SALES GROWTH, BOARD SIZE, DIVIDEND PAYMENT, DAN CASH FROM OPERATION TERHADAP CASH HOLDING - Panji Satria Panalar, Agustin Ekadjaja (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This research was conducted in order to determine whether the sales growth, board size, dividend payment, and cash from operation affect the cash holding on manufacturing companies listed in Indonesia Stock Exchange, especially in 2015-2017. The number of samples that be used were 93 data is determined using purposive sampling, the sample of data was obtained is financial statements from www.idx.co.id. The data in this study were processed using SPSS 21 by analyzing descriptive statistical tests, classic assumption tests and hypothesis testing. Cash from operation have an influence on cash holding, while the sales growth, board size, and dividend payment have no influence on cash holding.